Understanding Decision Making Processes in Sustainable Construction Practices at Urban Infrastructure Projects - Muslimatul Mufida; Hariyono Seputro Youngky Pratama; Taufikkurrahman (Jurnal Ragam Pengabdian, 2026)
Urban infrastructure development in metropolitan cities such as Jakarta is increasingly characterized by high complexity arising from the integration of environmental sustainability demands, regulatory compliance, resource limitations, and pressures for cost and time efficiency. In this context, decision- making processes extend beyond purely technical considerations and reflect multidimensional interactions among actors, interests, and institutional frameworks that influence the implementation of sustainable construction practices. This study examines the decision-making mechanisms underlying the adoption of sustainable construction practices in urban infrastructure projects, with emphasis on the roles of key actors, decision rationalities, and trade-off dynamics throughout the project life cycle. A qualitative case study approach was employed, focusing on a single urban infrastructure project in Jakarta. Data were collected through semi-structured interviews with six purposively selected key actors, namely the project manager, site engineer, sustainability officer, main contractor representative, planning or supervision consultant, and a government representative as the project owner, complemented by an analysis of project documents and relevant regulatory frameworks. The data were analyzed using thematic analysis to identify decision-making patterns and inter- actor relationships. The findings indicate that decision-making in sustainable construction is shaped by continuous negotiation among regulatory pressures, economic considerations, technical readiness, and varying levels of actors’ commitment to sustainability agendas, which result in compromises between environmental performance and project efficiency. The novelty of this study lies in its empirical mapping of decision-making processes as dynamic, contextual, and actor-centered practices, contributing conceptually to sustainable construction studies and offering practical implications for improving governance quality in urban infrastructure projects.